LTE-advanced air interface technology - Zhang, Xincheng (CRC Press, 2013)
Opportunities are at hand for professionals eager to learn and apply the latest theories and practices in air interface technologies. Written by experienced researchers and professionals, LTE-Advanced Air Interface Technology thoroughly covers the performance targets and technology components studied by 3GPP for LTE-Advanced. Besides being an explanatory text about LTE-Advanced air interface technology, this book exploits the technical details in the 3GPP specification, and explains the motivation and implication behind the specifications. After a general description of wireless cellular techno.